PENGARUH KEBIASAAN DALAM BELAJAR TERHADAP HASIL BELAJAR FIQIH SISWA KELAS VII MTS PARMIYATU WASSA’ADAH SAMBIREJO TIMUR TAHUN PEMBELAJARAN 2020/2021 - Arifa Pratami, Ahmad Khaidir, Tuti Alawiyah, (Fakultas Agama Islam, 2022)
Student study habits are an activity or activity carried out by students in learning activities, in the form of study habits at school and at home. Study habits carried out by students are different. In other words, study habits are the ways in which students learn to acquire knowledge. Study habits are positively related to student learning outcomes. The better the student's study habits, the better the value of student learning outcomes. The learning outcomes that are focused on in this study are cognitive learning outcomes in Fiqh subjects. Fiqh is an effort to guide and care for students to understand what is contained in Islam as a whole, to live up to the meaning and purpose and objectives and in the end be able to practice it and make Islamic teachings as views and guidelines in carrying out their lives. This study aims to describe habits in learning. Fiqh learning outcomes, and the influence of habits in learning on Fiqh learning outcomes for seventh grade students at MTs Parmiyatu Wassa'adah for the 2020/2021 academic year. The population in this study were all seventh grade students. The research sample was set at 23 students. The sample was determined using a purposive technique. This research method is a descriptive correlational technique with a quantitative approach. The data collection tool used is a habitual questionnaire in learning and Fiqh learning outcomes in the form of final exam scores in odd semesters. The conclusions obtained from this study are: students' study habits get an average value of 73.16 including in the medium rank, students' Fiqh learning outcomes get an average value of 73.57 including in the medium category and study habits have an influence of 25.81% on the Fiqh learning outcomes of seventh grade students at MTs Parmiyatu Wassa'adah Sambirejo Timur. The better the student's study habits, the better the value of student learning outcomes. Based on the calculation of the regression equation, it can be explained that the regression coefficient of the student habit variable in learning is 0.043; This means that if the habit of learning has increased by 1 unit, the learning outcomes of Fiqh will increase by 0.043. The increase in the value of Fiqh learning outcomes to 73.57.